2021
DOI: 10.1038/s41529-021-00168-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular scale insights into interaction mechanisms between organic inhibitor film and copper

Abstract: A model experimental approach, providing molecular scale insight into the build up mechanisms of a corrosion inhibiting interface, is reported. 2-mercaptobenzimidazole (2-MBI), a widely used organic inhibitor, was deposited from the vapor phase at ultra-low pressure on copper surfaces in chemically-controlled state, and X-ray photoelectron spectroscopy was used in situ to characterize the adsorption mechanisms upon formation of the inhibiting film. On copper surfaces prepared clean in the metallic state, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
(66 reference statements)
3
15
0
Order By: Relevance
“…Copper spectrum reveals a peak, observed at 932.3 eV, which is characteristic for 0‐and 1‐valent copper. Previous reports on copper complexes with N ‐containing heterocycles, such as benzotriazole, 44 2‐mercaptobenzothiazole, 45–47 5‐mercaptopentyl‐3‐amino‐1,2,4‐triazole, 48,49 2‐mercaptobenzimidazole 50 suggest annotation of this peak to the copper bonded with nitrogen. We assume that a single valent copper PTI lattice intercalation goes through coordination of copper at random bridging nitrogens.…”
Section: Resultsmentioning
confidence: 87%
“…Copper spectrum reveals a peak, observed at 932.3 eV, which is characteristic for 0‐and 1‐valent copper. Previous reports on copper complexes with N ‐containing heterocycles, such as benzotriazole, 44 2‐mercaptobenzothiazole, 45–47 5‐mercaptopentyl‐3‐amino‐1,2,4‐triazole, 48,49 2‐mercaptobenzimidazole 50 suggest annotation of this peak to the copper bonded with nitrogen. We assume that a single valent copper PTI lattice intercalation goes through coordination of copper at random bridging nitrogens.…”
Section: Resultsmentioning
confidence: 87%
“…Our results confirm that Cu dissolution is not hindered for 12% of the surface sites at the emergence of a Σ9 CSL GB. A possible scenario is that a multilayer of MBT is formed at the surface, as evidenced by XPS measurements 17,33 . The Cu atoms which extraction is not hindered have a high probability to bind with a MBT molecule in the layers above the first, strongly chemisorbed layer.…”
Section: Defect Formation Energymentioning
confidence: 99%
“…Recently, the adsorption of MBT on metallic and pre-oxidized Cu(111) model surfaces has been investigated, both experimentally and theoretically. It was shown that MBT adsorbs on metallic and preoxidized copper and forms organic multi-layers thereon [17][18][19] . DFT calculations also revealed that these molecules are able to heal local de-passivated zones exposing the bare metal next to the protecting oxide 20 , with similar adsorption behavior than 2-Mercaptobenzimidazole (MBI) molecule 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus a stable molecular film forming a barrier that protects the copper surface from its environment is stabilized by chemisorption. 29,34,36,39,40,43,45,48,50,52,[55][56][57][58][59][60][61][62][63][64] For MBT, a Cu-MBT surface film would form with thickness depending on the pH of the medium, 36,37 ranging from only a monolayer film in conditions where a stable Cu 2 O oxide is formed (pH > 4) to the formation of multilayers in acidic conditions where no stable Cu 2 O film can be formed (pH < 3). 48,52 The proposed formation mechanism is one where surface ions of Cu(I) react to adsorbed MBT.…”
mentioning
confidence: 99%